2008
DOI: 10.1093/heapro/dan025
|View full text |Cite
|
Sign up to set email alerts
|

Preventing childhood obesity: the sentinel site for obesity prevention in Victoria, Australia

Abstract: SUMMARYIn spite of greater awareness of the need for action to reduce obesity, the evidence on sustainable community approaches to prevent childhood and adolescent obesity is surprisingly sparse. This paper describes the design and methodological components of the Sentinel Site for Obesity Prevention, a demonstration site in the BarwonSouth West region of Victoria, Australia, that aims to build the programs, skills and evidence necessary to attenuate and eventually reverse the obesity epidemic in children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…58 The site includes intervention, training, evaluation, and monitoring actions in order to strengthen the capacities of communities regarding the promotion of a healthy diet, physical activity, and maintaining the appropriate weight in children. An internet-based diet program DASH has been used to verify behavioral changes associated with eating habits, in order to examine the effects on weight and blood pressure.…”
Section: New Technological Approachesmentioning
confidence: 99%
“…58 The site includes intervention, training, evaluation, and monitoring actions in order to strengthen the capacities of communities regarding the promotion of a healthy diet, physical activity, and maintaining the appropriate weight in children. An internet-based diet program DASH has been used to verify behavioral changes associated with eating habits, in order to examine the effects on weight and blood pressure.…”
Section: New Technological Approachesmentioning
confidence: 99%
“…[37][38][39][40][41][42] Four major statewide initiatives aiming to impact on nutrition, physical activity and/or obesity prevention in communities and settings relevant to early childhood in Victoria have been in operation during the last decade. 37,38,41 The programmes include one with a focus on food service in child care centres, 38 one multicomponent programme, 37 which included nutrition, physical activity and breastfeeding promotion strategies, to complement ongoing efforts to promote breastfeeding initiation and duration across the state 43 and one programme focused on oral health promotion which included comprehensive strategies to promote healthier snacks and water consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Further details of sampling and recruitment procedures for this study have been reported previously. 22,23 Measures Anthropometric measures. Child height and weight were measured by trained researchers using standard methods.…”
Section: Materials and Methods Samplementioning
confidence: 99%
“…19,23 The school questionnaire comprised 46 items. The variables selected to use in the modelling to represent the school level were the presence of written school policies for healthy eating (yes/no), and physical activity (yes/no).…”
Section: School Measuresmentioning
confidence: 99%